Incorporating Arabic words in English language teaching: teachers’ perspective - Othman, Khairiah; Abdul Hamid, Zuridah Hayati (2009)
The paper aims to highlight the need to incorporate certain Arabic words in the teaching of English to Muslim students. Based on al-Faruqi’s framework on Islamic English for Islamic vocabulary to be retained in their Arabic form in an effort to maintain the original meanings, a set of questionnaires was distributed to teachers who were teaching English in an Islamic institution to gather their perspectives as to whether there was a need for Islamic English to be incorporated in the teaching of English to Muslim learners. The findings indicated that although half of the teachers did not know what was meant by Islamic English, they have been using Arabic words in their classes. A majority of them even encouraged the use of Arabic words to be incorporated in English classes. They also believed that the students were receptive to the idea. This paper has pedagogical implications to ESL teachers who teach English to Muslim learners. Keywords: Islamic English, Islamization of knowledge, teachers’ attitudes, English as a second language (ESL), Muslim learners